การพัฒนานิยายโดยใช้เทคนิคการเล่าเรื่องเป็นเครื่องมือจัดการความรู้ เพื่อส่งเสริมการเรียนรู้ของผู้เรียนในรายวิชาการจัดการความรู้ - วาณิชวศิน, พัชรา (วารสารวิชาการศึกษาศาสตร์ ศรีนครินทรวิโรฒ, 2017)
บทคัดย่อ การวิจัยมีวัตถุประสงค์เพื่อ 1) พัฒนานิยายโดยใช้เทคนิคการเล่าเรื่องเป็นเครื่องมือจัดการความรู้ 2) ตรวจสอบการเรียนรู้ของผู้เรียนในรายวิชาการจัดการความรู้ กลุ่มตัวอย่างแบบเฉพาะเจาะจงคือ นิสิตระดับปริญญาตรีจำนวน 49 คน เครื่องมือคือ 1) นิยาย 2) แบบสอบถามความเหมาะสม 3) แบบทดสอบผลสัมฤทธิ์ทางการเรียน 4) แบบสอบถามความพึงพอใจของผู้เรียน สถิติวิเคราะห์ข้อมูลได้แก่ การวิเคราะห์เนื้อหา ค่าเฉลี่ย ค่าเบี่ยงเบนมาตรฐาน และสถิติทดสอบที (t-test) ผลการวิจัยพบว่า (1) ผู้วิจัยนำแนวคิดสำคัญจากนิยาย เทคนิคการเล่าเรื่อง การจัดการความรู้และหลักสูตรมาพัฒนาเป็นนิยายจำนวน 9 ตอน 66 หน้าครอบคลุมองค์ความรู้ในตนและเชิงประจักษ์เกี่ยวกับหลักสูตร ซึ่งการพัฒนานิยายมี 6 ขั้นตอนดังนี้ 1) เลือกหัวข้อเรื่อง 2) นำแนวคิดสำคัญมาจัดทำเป็นนิยายและใช้เป็นเนื้อหาในนิยาย 3) วางโครงเรื่องและแก่นสำคัญของเรื่อง 4) สร้างเหตุการณ์นำสู่เรื่องเล่า 5) นำเสนอตัวละคร และ 6) เขียนเล่าเรื่องในรูปแบบนิยาย ทั้งนี้ความเหมาะสมของนิยายได้รับการประเมินจากผู้เชี่ยวชาญว่าอยู่ในเกณฑ์เหมาะสม ( = 4.75, S.D. = 0.22) ระดับมากที่สุด ด้านเนื้อหา โครงสร้างและการนำเสนอ (2) สำหรับการเรียนรู้ของผู้เรียนในรายวิชาการจัดการความรู้ค่าเฉลี่ยคะแนนก่อนใช้อยู่ที่ 67.15 และหลังใช้อยู่ที่ 74.42 จากคะแนนเต็ม 100 คะแนนโดยค่าเฉลี่ยหลังใช้สูงกว่าก่อนใช้อย่างมีนัยสำคัญทางสถิติที่ระดับ 0.05ความพึงพอใจของผู้เรียนอยู่ในระดับสูง ( = 4.12, S.D. = 0.54) โดยผู้เรียนพบว่า นิยายเป็นวิธีจัดการความรู้ที่ดี แปลกใหม่ สนุกสนาน น่าสนใจและสอดแทรกความรู้สำคัญที่ทำให้เกิดการเรียนรู้ รวมทั้งเป็นรูปแบบการจัดการความรู้ที่ดี ผลวิจัยสรุปได้ว่า นิยายสามารถใช้เป็นเครื่องมือจัดการความรู้ที่ทรงพลังในการถอด แลกเปลี่ยนและถ่ายทอดความรู้ที่ง่ายต่อความเข้าใจและน่าสนใจที่จะเรียนรู้โดยผู้เรียนสามารถเรียนรู้ได้ดียิ่งขึ้นส่งผลให้การเรียนรู้ดีขึ้นทั้งผลสัมฤทธิ์และความพึงพอใจ คำสำคัญ : นิยาย, เทคนิคการเล่าเรื่อง, เครื่องมือการจัดการความรู้, การเรียนรู้ของผู้เรียน ABSTRACT The purposes were to:1)develop a novel using storytelling technique as a knowledge management tool, and 2) examine student learning in knowledge management subject after applying a developed novel.The purposive sample group was 49 undergraduate students.The research instruments were 1) a developed novel, 2) a questionnaire collecting expert opinions towards appropriateness of a developed novel, 3) pre-test and post-test towards student achievement, and 4) a questionnaire collecting student’s opinions towards satisfaction. Statistical methods used were content analysis, mean, standard deviation and t-test. The research results were summarized as following: 1) A developed novel was based on the key concepts of novel, storytelling technique, knowledge management and curriculum. It consisted of 9 chapters with 66 pages covering tacit and explicit knowledge of curriculum. There were 6 main steps to develop a novel. First, the topic was chosen. Second, key concepts were used as content and design. Third, the plot and theme were planned. Fourth, the sceneswere set. Fifth, the characters were introduced. Sixth, the story was written in a form of a novel. A developed novel was then verified by experts as appropriate ( = 4.75, S.D. = 0.22) at a very high level in its content, structure and presentation. 2) For student learning in knowledge management subject, scores of student achievement before and after applying a developed novel was 67.15 and 74.42 of 100, respectively. The posttest scores were higher significantly than the pretest scores at 0.05 level of significance. Student satisfaction towards a developed novel was at a high level ( = 4.12, S.D. = 0.54). Students found it as a new, fun, interesting, integrated with essential knowledge way to learn and it was also a good form of knowledge management in their opinions. In conclusion, a developed novel can be used as a powerful knowledge management tool to capture, share and transfer knowledge, which was easy to understand and motivating for students to learn in knowledge management subject. Students can perform better, which resulted in enhanced student learning both achievement and satisfaction. Keywords : Novel, Storytelling Technique, Knowledge Management Tool, Student Learning.